PENGELOLAAN SAMPAH KAMPUS 2 UIN WALISONGO SEMARANG (TINJAUAN MULTIDIMENSI) - Anif Rizqianti Hariz; Sulaiman Sulaiman (EnviroScienteae, 2022)
The waste in the trash is still mixed, and in its management, the waste is not processed and transported immediately to TPA Jatibarang. Sustainable waste management needs to pay attention to 5 aspects of waste management, namely operational technical aspect, institutional aspect, financing aspect, legal and regulatory aspect, and community participation aspect. The purpose of this study is to obtain an integrated waste management concept from the 5 aspects of waste management. The method used in this research is descriptive qualitative, the data is taken using observation, interview, and documentation techniques. It is known that the waste generation on campus 2 is 129.36 kg / day with a volume of 1,903.98 l / day. Composition of food waste 15.74%; wood and garden waste 48,12%; plastic 9,19%; metal 0.20%; paper / cardboard 9.05%; fabrics / textiles 0.30%; glass / glass 0.41%; rubber / leather 0.42%; and other 16,56%. The operational technique of waste management is planned to use 5 separate bins based on waste types, collection using a three-wheeled open motorbike, transfer to TPST on Kampus 2, then composting the food waste and garden waste. Plastic, paper, metal, glass, and rubber can be deposited into Bank Sampah at UIN Walisongo, while cloth and other waste are disposed to TPA Jatibarang. On the regulatory aspect, there are no regulations at the university level governing waste management. In the institutional aspect, it is necessary to carry out technical training for cleaning personnel regarding solid waste management, as well as institutional strengthening. In the aspect of financing, the cost of waste management is budgeted in the Rencana Belanja dan Anggaran which is proportional to the generation of waste every year. In community participation aspect, it is necessary to conduct socialization and education to the entire academic community of UIN Walisongo to increase awareness and participation in waste management.